2015
DOI: 10.1002/ajmg.c.31426
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue, Ehlers–Danlos syndrome(s), and head and cervical pain

Abstract: Ehlers-Danlos syndrome (EDS) is an umbrella term for a growing group of hereditary disorders of the connective tissue mainly manifesting with generalized joint hypermobility, skin hyperextensibility, and vascular and internal organ fragility. In contrast with other well known heritable connective tissue disorders with severe cardiovascular involvement (e.g., Marfan syndrome), most EDS patients share a nearly normal life span, but are severely limited by disabling features, such as pain, fatigue and headache. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 102 publications
3
31
0
Order By: Relevance
“…Much like headaches in the general population, headaches in hEDS vary by type and severity [Jacome, ; Murray et al, ; Neilson and Martin, ; Castori et al, ]. Headache itself has been show to occur in a larger portion of EDS patients (multiple types of EDS) as compared to historical controls [Sacheti et al, ].…”
Section: Clinical Descriptionmentioning
confidence: 99%
“…Much like headaches in the general population, headaches in hEDS vary by type and severity [Jacome, ; Murray et al, ; Neilson and Martin, ; Castori et al, ]. Headache itself has been show to occur in a larger portion of EDS patients (multiple types of EDS) as compared to historical controls [Sacheti et al, ].…”
Section: Clinical Descriptionmentioning
confidence: 99%
“…Headaches, in particular migraine, was higher in prevalence and more often more disabling than the control population (N = 232). Castori et al [] reported the incidence of headaches in no less than 1/3 of patients with EDS with migraines as the most common headaches. Other possible causes of headaches include tension‐type headache, new daily persistent headache, temporomandibular joint dysfunction (TMD), Chiari malformation, cervicogenic, neck–tongue syndrome, and medication related [Neilson and Martin, ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…EDS patients commonly suffer a variety of headache types [Jacome, ; Martin and Neilson, ; Castori et al, ]. These include headaches due to migraines, muscle tension, intracranial hypertension, craniocervical instability, and cervical spine disorders, temporomandibular joint disease, carotid dissection, and other physical conditions.…”
Section: Headache In Ehlers–danlos Syndromementioning
confidence: 99%
“…Migraine, common in the general population, is more prevalent in women [Nappi and Nappi, ]. Migraine is also more prevalent among EDS which also has a female predilection [Bendik et al, ; Castori and Voermans, ; Castori et al, ]. Therefore, EDS may be considered a risk factor for migraine.…”
Section: Headache In Ehlers–danlos Syndromementioning
confidence: 99%